Evaluation of the efficacy of Chinese herbal medicine and acupuncture for the prevention of mental disorders in interstitial cystitis patients: A nationwide population-based study. Issue 30 (24th July 2020) - Hung, Hao-Hsiu; Chen, Wen-Chi; Chen, Yung-Hsiang; Chiu, Lu-Ting; Chen, Huey-Yi
Abstract : Abstract: Traditional Chinese medicine (TCM) is commonly used for urinary symptoms in Eastern countries. Since there are few effective treatments available for patients with interstitial cystitis/bladder pain syndrome (IC/BPS), the psychological burden leads to increased healthcare-seeking behavior. Some patients may therefore seek TCM treatment for related urinary symptoms. Due to limited clinical research evaluating the effects of TCM on IC/BPS, we conducted a nationwide population-based cohort study to investigate the relationship between TCM and mental disorders among these patients. The IC/BPS cohort and its matched non-IC/BPS comparison cohort were recruited from the National Health Insurance (NHI) Research Database between 2000 and 2011. Patients with the use of Chinese herbal medicine (CHM) granules or acupuncture over 90 days per year were enrolled as the TCM users. Multivariable Cox proportional hazards models were used to evaluate the hazard ratio (HR) of mental disorders related to interstitial cystitis. The incidence of mental disorders in the 2 cohorts was assessed with Kaplan–Meier curves. A total of 1123 patients with IC/BPS and 4492 matched non-IC/BPS subjects were included in this study. The IC/BPS cohort demonstrated higher incidence rate of mental disorders than the cohort without IC/BPS (adjusted HR: 2.21, 95% confidence interval [CI]: 1.73–2.81). There was no statistically significant difference in the risk of mental disorders between IC/BPS patients with and without CHM granules or acupuncture treatment (adjusted HR: 0.99, 95% CI: 0.58–1.68). Our results indicated that CHM and acupuncture showed insignificant efficacy in the prevention of mental disorders in IC/BPS patients.